Post partum haemorrhage: Prevalence, morbidity and management pattern in Dhulikhel Hospital - Dongol, AS; Shrestha, A; Chawla, CD (Kathmandu University Medical Journal, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: Post partum haemorrhage (PPH) is the leading cause of maternal death worldwide. PPH occurs in up to 18% of total births. Among different factors, PPH due to uterine atony is the primary and direct cause of maternal mortality comprising about 90%. Objective: The objective of the present study was to assess the prevalence, morbidity and management pattern of PPH in Dhulikhel Hospital. Materials and methods: Hospital based retrospective study was carried out at Kathmandu University School of Medical Science, Dhulikhel Hospital from the period of January 2007 till October 2009. The study group included total of 60 patients. All women who had PPH both primary and secondary were studied. Information regarding total number of deliveries obtained from Obstetrics ward. The cases with PPH were identified and detail records were reviewed using standard format. The main outcome measures used for the analysis were amount of blood loss, cause of PPH and treatment methods. Results: In Dhulikhel hospital, from January 2007 till October 2009 a total of 3805 deliveries took place. Out of which 60 women had PPH. The prevalence was 16/1000 deliveries. There are 41 (68.3%) cases of primary PPH and 19 (31.7%) cases of secondary PPH. PPH was found more in home deliveries, unbooked case and in multiparas. The mean blood loss was 1055ml. As an aetiology, retained placenta and retained placental bits of tissue was found in 37(61.7%) cases, atonic uterus in 10 (16.7%) cases, genital tract trauma in 8(13.3%), sepsis of genital tract in 3(5%), case of ruptured uterus in one case and a case of angle bleeding from previous uterine scar following caesarean section. Among all 15 (25%) cases underwent manual removal of placenta, 5(8.3%) underwent controlled cord traction, 3 (5%) underwent manual removal of placenta followed by check curettage in cases of retained placenta, 16 (26.7%) cases were managed by check curettage for retained bits of placental tissue and membrane. Trauma in genital tract was managed by repair of trauma in 6 (10%) cases. Hysterectomy was required in 3 (5%) cases. Conservative management with uterotonics only required in 12 (20%) cases. Conclusion: Active management of third stage of labour can prevent PPH so delivery by skilled hand in hospital should be promoted. Secondary PPH besides primary can result in significant maternal morbidity. It also deserves similar attention. Key words: Atonic uterus; Postpartum haemorrhage DOI: 10.3126/kumj.v8i2.3561 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 212-215